Greenland, view of valley at Kjerulf Fjord annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
August 1, 1931. Kjerulfs [Kjerulf] Fjord. Extreme inner end: 'Right Valley' - south side - from eastern terminal showing glaciers and piled up earth like mine-dump. See photos 22-D-18 & 24-F-2. Background on right: N.E. terminal of 'Right Valley'. Photo taken from floor of southern end of 'Main Valley' looking in S.W. direction and showing stream of 'Right Valley' at mouth, at junction of all three valleys.